Complete regression of melanocytic nevi: clues for proper diagnosis - Cintra, Maria Leticia; Souza, Elemir Macedo de; Fernandes, Fernanda Mouro (São Paulo Medical Journal, 1994)
A histopathological study of a distinct papule isolated from a patient’s neck is reported and compared to 80 melanocytic nevi. The histogenesis of this unique tumor indicates that it probably represents the residual of a melanocytic nevus in wich nevi cells have disappeared but fat infiltration and fibrosis of the dermis and the typical aspects of other cutaneous elements persisted. The finding of focal acantholytic dyskeratosis in multiple foci of the lesion may indicate melanocytic cells regression. Lesions with the histopathological appearence of melanocytic nevi, even in the absence of nevi cells, may be discovered scrutinizing the associated alterations.